Identification of patients who may benefit the most from adjuvant chemotherapy following resection of incidental gallbladder carcinoma. Issue 4 (26th January 2021) - Xiang, Jun‐Xi; Zhang, Xu‐Feng; Weber, Sharon M.; Poultsides, George; Fields, Ryan C.; Hatzaras, Ioannis; Weiss, Matthew; Scoggins, Charles; Idrees, Kamron; Shen, Perry; Maithel, Shishir K.; Pawlik, Timothy M.
Abstract: Background: To develop a scoring system to identify the subset of patients who may benefit the most from adjuvant chemotherapy following curative‐intent resection for incidental gallbladder cancer (IGBC). Methods: A novel scoring system was utilized to stratify patients relative to overall survival (OS), as well as potential benefit from adjuvant chemotherapy following curative resection for IGBC. Results: Among 266 patients with IGBC, a total of 99 (37.2%) patients received adjuvant chemotherapy. Five risk factors were used to develop an integer‐based score to predict OS. Risk of death at 5‐years incrementally increased among patients in the low ( n  = 42, 69.0%), medium ( n  = 64, 56.3%) and high‐risk groups ( n  = 40, 30.0%) (median OS, 99.4 vs. 33.5 vs. 15.6 months, all p  < .001). Use of adjuvant chemotherapy did not provide a survival benefit among patients in the low‐risk group (median survival, 99.4 vs. 60.7 months, p  = .56). In contrast, utilization of adjuvant chemotherapy was associated with an improvement in survival among medium‐ (median survival, 21.7 vs. 59.5 months, p  = .04) and high‐risk patients (median survival, 11.6 vs. 20.1 months, p  = .01). Conclusions: While low‐risk patients did not benefit from adjuvant chemotherapy, individuals with medium or high‐risk scores had an improved survival with the utilization of adjuvant chemotherapy.